2008
DOI: 10.3201/eid1403.071250
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Novel Parainfluenza Virus and Clinical Relevance in 2 Bottlenose Dolphin (Tursiops truncatus) Populations

Abstract: Evidence of PIV exposure was detected in free-ranging and managed dolphin populations living along 2 US coastlines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…9 Given that managed death and was considered a possibile contributing factor. 72 An enterovirus was cultured from a tongue lesion of an ex situ bottlenose dolphin with hematologic signs of inflammation. 72 An enterovirus was cultured from a tongue lesion of an ex situ bottlenose dolphin with hematologic signs of inflammation.…”
Section: Parasitic Diseasesmentioning
confidence: 99%
“…9 Given that managed death and was considered a possibile contributing factor. 72 An enterovirus was cultured from a tongue lesion of an ex situ bottlenose dolphin with hematologic signs of inflammation. 72 An enterovirus was cultured from a tongue lesion of an ex situ bottlenose dolphin with hematologic signs of inflammation.…”
Section: Parasitic Diseasesmentioning
confidence: 99%
“…Specifically, pneumonia was observed in 28 % of the children positive for PIV-3 [3]. A study which monitored the PIV seroconversion in T. truncatus indicated that 3 out of 4 of the animals that died within 30 days of seroconversion had a fungal or bacterial coinfection in their lungs [7]. Polymicrobial infections are common across species, especially the association of PIV with other bacterial or fungal microbes.…”
Section: Discussionmentioning
confidence: 97%
“…Similar clinical symptoms are observed during PIV-3 infection in different species. An early clinical sign of BRDC in cattle is loss of appetite, which was a commonly reported behavioral abnormality (54 %) in dolphins with antibodies to PIV [5,7]. The bottlenose dolphin in which TtPIV-1 was isolated from exhibited raspy breaths and cream-colored exudate from the blowhole [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to obtain unequivocally negative serum samples from wildlife species (Nollens et al, 2006; Venn-Watson et al, 2008). In the absence of sufficient unequivocal control sera we were unable to determine a positive:negative cut-off value for the assay.…”
Section: Discussionmentioning
confidence: 99%